Regulating work and welfare of the future: Towards a new gender contract? - Jacqueline O'Reilly; Claudia Spee (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
This paper starts off by briefly considering some of the problems of future studies; it discusses how the origins and principles of the systems of regulation and security have generated different employment systems in Europe. The concept of employment systems allows us to identify how the future of work may well be managed in different ways according to the capacity and constraints of national and European actors. The paper focuses on the characteristics and changes in European regulatory systems of labour and social welfare. Two key developments are identified in these areas. First there are trends to decentralise collective bargaining and to encourage a trade off between labour flexibility and employment security. Second, there have been trends towards a decentralisation and outsourcing of state monopolies and attempts to develop new forms of caring. The prospects these trends imply for regulating the work of the future are discussed in relation to the development of a new social and gender contract.
Keywords: 330